Restrictions on the Right to Freedom of Expression in Public from the Perspective of Rule of Law - Edi Sofwan (International Journal of Community Service (IJCS), 2026)
Freedom of expression is a foundational human right and a core precondition for democratic governance, transparency, and public participation. Nevertheless, international and domestic legal orders consistently recognize that this right is not absolute and may be restricted under certain conditions. This article conducts a qualitative, normative–juridical analysis of restrictions on the exercise of freedom of expression in public, examined through the lens of the rule of law. Drawing on international human rights instruments, particularly Article 19 of the International Covenant on Civil and Political Rights (ICCPR) and its “three-part test”, as well as constitutional and statutory norms in Indonesia, the article develops a set of rule-of-law-based criteria for assessing the legitimacy of restrictions. Qualitative doctrinal analysis is combined with thematic examination of case law, statutory frameworks, and critical commentary. The findings show a persistent tension between justified, narrowly tailored limitations and broader, vague or disproportionate restrictions that risk converting the rule of law into “rule by law”. The article concludes by proposing normative benchmarks and practical safeguards to ensure that any limitations on public expression remain compatible with democratic constitutionalism and the rule of law..